2003
DOI: 10.1606/1044-3894.101
|View full text |Cite
|
Sign up to set email alerts
|

Caring Relationships as a Protective Factor for At-Risk Youth: An Ethnographic Study

Abstract: The resiliency literature documents that adult caring relationships are key to the development of resilience in children. The present ethnographic study of 23 youths' perceptions of caring adults explored the meanings they ascribe to caring relationships in helping them face adversity. The study confirmed that caring adults can serve as a protective factor for at-risk youth. In addition, the study delineated seven characteristics of those caring relationships: trust, attention, empathy, availability, affirmati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 4 publications
5
29
0
8
Order By: Relevance
“…To face the immense challenge of day-to-day homeless existence, these young people must learn to adjust to the hardships associated with life on the streets. While acknowledging the difficulties associated with unstable living situations, research has suggested that innate capabilities of resiliency enable individuals to overcome the adverse effects of hardship (Laursen & Birmingham, 2003). This point of view encourages a balanced examination of individuals' limitations and strengths as challenges are regarded from a position of empowerment.…”
Section: Introductionmentioning
confidence: 99%
“…To face the immense challenge of day-to-day homeless existence, these young people must learn to adjust to the hardships associated with life on the streets. While acknowledging the difficulties associated with unstable living situations, research has suggested that innate capabilities of resiliency enable individuals to overcome the adverse effects of hardship (Laursen & Birmingham, 2003). This point of view encourages a balanced examination of individuals' limitations and strengths as challenges are regarded from a position of empowerment.…”
Section: Introductionmentioning
confidence: 99%
“…Their support strengthened my resilience-my ability to "achiev[e] positive outcomes despite risk" (J. E. Brooks, 2006, p. 69). This is in keeping with resiliency literature which suggests that caring adult relationships can serve as protective factors for at-risk youths (Brooks, 2006;Laursen & Birmingham, 2003). In a study of middle-school students, researchers found that "perceived caring from teachers predicted motivational outcomes, even when students' current levels of psychological distress and beliefs about personal control, as well as previous (6th grade) motivation and performance, were taken into account" (Wentzel, 1997).…”
Section: The Scholarsupporting
confidence: 65%
“…Once recruited, training in positive youth development principles would be helpful to encourage a strengths-based approach to juvenile care work (Butts et al 2005). As part of this training, staff should learn techniques to develop rapport with challenging youth (Laursen and Birmingham 2003). Staff training also should cover the potential pitfalls, suggested by this and other studies, that come from being too directive in approaches to problem-solving and unintentionally setting up correctional paradoxes.…”
Section: Discussionmentioning
confidence: 99%